Transformation of a formula

melodyw

New member
Joined
Feb 4, 2017
Messages
5
Non-affine function into affine function

Help. How would you transform 2 x Co^(1/2) x exp(-ktCo^(1/2))=C^(1/2) x (1+exp(-ktCo^(1/2)) into function y=ax+b, concentration C should be y, and time t should be x.
 
Last edited:
Help. How would you transform 2 x Co^(1/2) x exp(-ktCo^(1/2))=C^(1/2) x (1+exp(-ktCo^(1/2)) into function y=ax+b, concentration C should be y, and time t should be x.

That function cannot be strictly linearized - i.e. you can linearize it if:

y = f1(C) and

x = f2(t)
 
Last edited by a moderator:
Yes, that is the first thing i have done but i get stuck with this part (1+exp(-ktCo^(1/2)) i don't know how to get t down?
If you write: u = kt√Co and v = √(2Co/C)
you would get:

v = eu + 1

Now y = v and

x = eu

and you get

y = x + 1
 
That function cannot be strictly linearized - i.e. you can linearize it if:

y = f1(C) and

x = f2(t)
so what should i do, how can i write it the best way, i managed to get C alone on the left side and the rest on the right side but t is still in exponent along with -k times square root from Co. What is x then? Can i write it like x=e^(t)?
 
If you write: u = kt√Co and v = √(2Co/C)
you would get:

v = eu + 1

Now y = v and

x = eu

and you get

y = x + 1
Do you think this is the only way?
Our professor is quite demanding then, we can't leave it that way. We also have to make a graph out of this and the units of measurement must fit.
 
Top